Intracerebroventricular calycosin attenuates cerebral ischemia-reperfusion injury in rats via HMGB1-dependent pyroptosis inhibition - Zhang, Yuhui; Wu, Qiguang; Pan, Yanjin; Xin, Min; Wang, Wenbo; Zhai, Xiaoya; Zhou, Peiquan; Zhang, Chong; Wang, Yong (Frontiers in Pharmacology, 2025)
IntroductionHMGB1-NLRP3 mediated pyroptosis was recently discovered to be a pathogenic cause of ischemic stroke. Our previous research has demonstrated the anti-inflammatory and anti-apoptotic properties of calycosin in mitigating cerebral ischemia-reperfusion injury (CIRI). However, its specific effects on HMGB1-NLRP3-mediated pyroptosis in ischemic stroke remain unclear. This study investigated the efficacy of calycosin in reducing pyroptosis-linked CIRI.MethodsIn vivo, a rat model of middle cerebral artery occlusion (MCAO) received varying doses of intracerebroventricular calycosin. Therapeutic efficacy was assessed using neurological deficit scores, TTC staining, H-E staining, Nissl staining, and immunohistochemistry. In vitro, HAPI microglial cells were subjected to oxygen-glucose deprivation/reoxygenation (OGD/R) and then treated with calycosin, HMGB1 siRNA, or MCC950. Cell survival was evaluated using the CCK8 assay. Ultrastructural changes were examined through transmission and scanning electron microscopy. Inflammatory cytokine levels were quantified by ELISA. The expression of pyroptosis-related proteins and genes was analyzed using Western blot and qRT-PCR.Results and DiscussionCalycosin significantly reduced neurological impairments and brain infarction in a dose-dependent manner, alleviated neuronal damage and decreased the expression of pyroptosis-related markers, including NLRP3, GSDMD, HMGB1, IL-1β, IL-18, and caspase-1. These results indicate that calycosin enhances microglial cell survival and mitigates pyroptotic damage by inhibiting NLRP3 inflammasome activation, suggesting its potential as a neuroprotective therapy for ischemic stroke through the modulation of the HMGB1-dependent pyroptosis pathway.